Topical use of Vancomycin in Craniotomy - Shakya, Bikram; KC, Bidur; Thapa, Amit (Nepal Journal of Neuroscience, 2019)
In neurosurgery, surgical site infections are major cause of morbidity and mortality. It has been significant burden in clinical practice, despite of best practices with or without use of antibiotics. Topical antibiotics are one potential method reducing the problem. In our study, we seek to evaluate the benefits of topical vancomycin. In this Institutional Review Board-approved retrospective observational study, patients who underwent neurosurgical intervention in Department of Neurological Surgery KMCTH enrolled retrospectively from October 1, 2014 to September 30, 2018. Patients in whom topical vancomycin powder applied intra operatively for post operative SSI prophylaxis and those without, comprising the vast majority of neurosurgical patients within the KMCTH, were examined. Patients presenting with infection, open wound, multiple scheduled surgeries, application of topical antibiotics other than vancomycin, or multiple antibiotics were excluded. Patients data were analyzed within the first 30 days aftersurgery. There were total 259 patients with 190 as control and 69 as cases. With all these surgeries undergone we had SSI in 5, 1.93% (p = <0.001) of emergency surgeries, where Vancomycin powder was not used. There were no surgical site infection in any of the cases where topical Vancomycin powder was used. Topical vancomycin is a safe, effective, and economical measure to prevent SSIs following craniotomy.